2018
DOI: 10.1002/ange.201811318
|View full text |Cite
|
Sign up to set email alerts
|

Schnelle Strukturaufklärung mikrokristalliner molekularer Verbindungen durch Elektronenbeugung

Abstract: Derzeit publizieren Chemiker aller Fachrichtungen ca. 50 000 Kristallstrukturen pro Jahr,von denen es sich bei der überwältigenden Mehrheit um Rçntgenstrukturen handelt. Wir setzen Elektronen-statt Rçntgenbeugung ein, um die Struktur zweier molekularer Verbindungen zu bestimmen. Zu diesem Zweckw urde ein EIGER-Hybridpixeldetektor an ein Transmissionselektronenmikroskop angebaut und so ein Elektronendiffraktometer konstruiert. Die Struktur eines neuen Methylenblauderivates wurde aus einem Kristall kleiner als 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
(77 reference statements)
1
23
0
2
Order By: Relevance
“…The possibility to see a residual potential related to hydrogen among heavy atoms like uranium is not as obvious as in previous works on materials containing lighter atoms. 11,14 However, this maximum corresponds to an ideal O-H distance and the hydrogen position is also supported by the DFT computations. Because of the presence of uranium, a further renement including hydrogen is not signicant and does not provide any improvement of further information.…”
Section: Single-crystal Electron Diffractionsupporting
confidence: 63%
“…The possibility to see a residual potential related to hydrogen among heavy atoms like uranium is not as obvious as in previous works on materials containing lighter atoms. 11,14 However, this maximum corresponds to an ideal O-H distance and the hydrogen position is also supported by the DFT computations. Because of the presence of uranium, a further renement including hydrogen is not signicant and does not provide any improvement of further information.…”
Section: Single-crystal Electron Diffractionsupporting
confidence: 63%
“…These principles are common for all types of crystals—organic, inorganic, and metal–organic. Opportunities and new advances continue to be reported, and a notable one is the complete crystal structure determination from powder quality microcrystals using electron diffraction and cryo transmission electron microscopy (ED‐TEM) …”
Section: Figurementioning
confidence: 99%
“…Like much of chemistry,the subject is oceanic in scope even as it is based on as mall number of guiding principles.T hese principles are common for all types of crystals-organic,i norganic,a nd metal-organic.O pportunities and new advances continue to be reported, and anotable one is the complete crystal structure determination from powder quality microcrystals using electron diffraction and cryo transmission electron microscopy (ED-TEM). [59,60] As as ubject with av ery promising future,t he following wish list for Crystal Engineering is inspired by Lippards article from 2000 in which he made such alist for chemistry. [61] It is interesting to note that 9out of 22 items in Lippardslist have to do with interactions between molecules and how they may be used to make extended domains of matter,generally with apre-desired property.Our wish list of ten items sets out what we feel are fundamental goals of the subject over the next decade.W el eave it to the reader to link the ways in which the attainment of these fundamental goals would help achieve the practical applications to which we allude in this Viewpoint.…”
Section: Solar Energy Materialsmentioning
confidence: 99%
“…Microcrystal electron diffraction (MicroED) is ideally suited to study protein nanocrystals of soluble proteins (17)(18)(19), membrane proteins (20)(21)(22) and small molecules (19,(23)(24)(25). However, recent investigations attempting to extract crystals from the viscous lipid-matrix have demonstrated that traditional sample preparation methods are ill-equipped to isolate well-diffracting crystals for MicroED experiments (26,27).…”
Section: Main Textmentioning
confidence: 99%